(untitled) - Capon, Noel (London, 1999)
This compilation of 60 case studies, covering 16 Asian countries and the Middle East, demonstrates the diversity of marketing problems faced by both domestic Asian and foreign corporations operating in Asia. The Asian countries are Bangladesh, China, Hong Kong, India, Indonesia, Japan, Kazakstan, Malaysia, Pakistan, the Phillipines, Singapore, South Korea, Sri Lanka, Taiwan, Thailand, and Vietnam. The cases cover a broad span of marketing issues, including industrial and consumer marketing, products, services, marketing strategy development, distribution, promotion, pricing, and intra-country and inter-country problems. An overview of each country provides useful background for the cases. The extensive range and breadth of cases makes this book a must-have for any instructor of International Marketing focusing on Asia
Keywords: Marketing; Case studies; Asia